God's new Israel : religious interpretations of American destiny - Cherry, Conrad, 1937- (Chapel Hill : University of North Carolina Press, 1998)
The belief that America has been providentially chosen for aspecial destiny has deep roots in the country's past. As both astimulus of creative American energy and a source of Americanself-righteousness, this notion has long served as a motivatingnational mythology. God's New Israel is a collection of thirty-one readings that trace the theme of American destiny under God through major developments in U.S. history. First published in 1971 and now thoroughly updated to reflect contemporary events, it features the words of such prominent and diverse Americans.
Anglo-Saxon Destiny and ResponsibilityPART SEVEN: CHALLENGES SINCE MID-CENTURY; America's World Role; Freedom's New Task; The Arrogance of Power; The Black American; Letter from Birmingham Jail; The Ballot or the Bullet; National Morals; Separation of Church and State: ""Christian Nation"" and Other Heresies; Creating a Healed World: Spirituality and Politics; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: United States -- History -- Philosophy; Political messianism -- United States; HISTORY -- State & Local -- General; RELIGION -- History; Philosophy; Political messianism; United States; Messianisme; History